Use of Copaifera multijuga for acute corneal repair after chemical injury: A clinical, histopathological and toxicogenetic study - Goncalves Dias, Fernanda Gosuen; Jorge, Adriana Torrecilhas; Pereira, Lucas de Freitas; Furtado, Ricardo Andrade; Ambrosio, Sergio Ricardo; Bastos, Jairo Kenupp; Ramos, Salvador Boccaletti; Chahud, Fernando; Gosuen Goncalves Dias, Luis Gustavo [UNESP]; Honsho, Cristiane dos Santos; Tavares, Denise Crispim (Elsevier B.V., 2017)
Copaiba oil is widely used in medicine, but there are no reports regarding its application in ophthalmology. Therefore, the objective of this study was to evaluate the clinical, histopathological and toxicogenetic effects of eye drops containing 0.1 and 0.5% of Copaifera multijuga Hayne oil on superficial corneal ulcers induced with alkali in the left eye of rats. For histological analysis, the percent reduction in ulcers and thickness of the corneal epithelium and stroma were evaluated 48 and 72 h after ulcer induction. Additionally, neovascularization and polymorphonuclear infiltration were classified in the stroma. The bone marrow micronucleus test was used for toxicogenetic assessment. None of the animals exhibited clinical signs of immediate ocular discomfort after instillation and the eye drops were harmless to the ocular surface. There was a significant difference in percent ulcer reduction and corneal stroma thickness between animals treated with the C. multijuga eye drops and untreated animals with corneal injury and the negative control, respectively, suggesting a healing effect of the oleoresin. Analysis of the thickness of the corneal epithelium at the two time points showed that the eye drops formulated did not significantly reduce the damage caused by alkali. The same was observed for the treatments with the reference drugs. No difference in stromal neovascularization or inflammatory infiltration was observed between the treated groups. The toxicogenetic results revealed the absence of cytotoxicity and genotoxicity of the treatments. In conclusion, the C. multijuga eye drops did not cause damage to the ocular surface under the present experimental conditions and corneal epithelization was similar to the conventional treatments. These results indicate that eye drops containing C. multijuga oleoresin are a promising option for the treatment of superficial keratitis.
Keywords: Copaifera multijuga; Hayne; Ulcerative keratitis; Corneal re-epithelization; Genotoxicity